The Non Operative Management of Bleeding Esophageal variclees: Endoscopic, Pharmacological or Both? - Farooqi, Javed Iqbal; Farooqi, Rukhsana Javed (Journal of Postgraduate Medical Institute, 2011)
Life threatening hemorrhage secondary to ruptured esophageal varices is a common complication of portal hypertension. The mortality rate associated with the index bleed is 35%; on the recurrent bleed, it is 50%. Between 10 - 20% per year will experience their first bleeding after varices are diagnosed and rebleeding may be experienced within two years in 70% of patients. While it is most important to control actively bleeding varices, it is also necessary to prevent effectively the index bleed (primary prevention), as well as recurrent variceal bleeding (secondary prevention).